Effect of bicyclopyrone herbicide on sweetpotato and Palmer amaranth (Amaranthus palmeri). (20th August 2020) - Lindley, Jennifer J.; Jennings, Katherine M.; Monks, David W.; Chaudhari, Sushila; Schultheis, Jonathan R.; Waldschmidt, Matthew; Brownie, Cavell
Abstract: Management options are needed to limit sweetpotato yield loss due to weeds. Greenhouse studies were conducted in 2018 in Greensboro, NC, and in the field from 2016 to 2018 in Clinton, NC, to evaluate the effect of bicyclopyrone on sweetpotato and Palmer amaranth (field only). In greenhouse studies, Covington and NC04-531 clones were treated with bicyclopyrone (0, 25, 50, 100, or 150 g ai ha −1 ) either preplant (PP; i.e., immediately before transplanting) or post-transplant (PT; i.e., on the same day after transplanting). Sweetpotato plant injury and stunting increased, and vine length and shoot dry weight decreased with increasing rate of bicyclopyrone regardless of clone or application timing. In field studies, Beauregard (2016) or Covington (2017 and 2018) sweetpotato clones were treated with bicyclopyrone at 50 g ha −1 PP, flumioxazin at 107 g ai ha −1 PP, bicyclopyrone at 50 or 100 g ha −1 PP followed by (fb) S -metolachlor at 800 g ai ha −1 PT, flumioxazin at 107 g ha −1 PP fb S -metolachlor at 800 g ha −1 PT, flumioxazin at 107 g ha −1 PP fb S -metolachlor at 800 g ha −1 PT fb bicyclopyrone at 50 g ha −1 PT-directed, and clomazone at 420 g ai ha −1 PP fb S -metolachlor at 800 g ha −1 PT. Bicyclopyrone PP at 100 g ha −1 fb S- metolachlor PT caused 33% or greater crop stunting and 44% or greater marketable yield reduction compared with the weed-free check in 2016 (Beauregard) and 2017 (Covington). Bicyclopyrone PP at 50 g ha −1 alone or fb S- metolachlor PT resulted in 12% or less injury and similar no. 1 and jumbo yields as the weed-free check in 2 of 3 yr. Injury to Covington from bicyclopyrone PT-directed was 4% or less at 4 or 5 wk after transplanting and marketable yield was similar to that of the weed-free check in 2017 and 2018.